APPLICATION OF EXTORTION AND THREAT CRIMINAL CASES ACCORDING TO LAW NO. 1 OF 2023: PENERAPAN PERKARA TINDAK PIDANA PEMERASAN DAN PENGANCAMAN MENURUT UU NO. 1 TAHUN 2023 - Fitasiani Laia, Fitasiani (UPMI Proceeding Series, 2023)
The are many dishonorable acts that have occurred among the community, with cases of extortion and forced threats, so according to law no. 1 of 2023 is implemented which becomes a sanction for those who violate this law. This research is a normative legal research that uses library law materials in the form of primary, secondary and tertiary legal materials, by carring out methods/techniques of studyng documents to be able to examine the problems under study. This application is based on the latest Law of 2023 in accor dance with article 482, and article 479, and lagal remedies regulated in article 483 and article 86 are additional sanctions. The judge’s considerations in imposing the sentence against the accused should not only be seen from the juridical aspect but also consider the sociological matters wich are the background to his actions both from his socio-cultural condition, psychological condition or his ability to be responsible.